1987
DOI: 10.1111/j.1440-1827.1987.tb00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Granular Cell Tumor of the Esophagus

Abstract: Malignant granular cell tumor of the esophagus found in a 70‐year‐old female was reported. Microscopically, the tumor showed a variety of the histology from compact proliferation of polygonal granular cells in pseudo‐epitheliomatous pattern to plexiform proliferation of elongated granular and fibroblastic cells in neuroflbromatous pattern, and the tumor cells frequently contained eosinophilic globules in the cytoplasm. Histochemically, argyrophilic neurofibrils in the stroma and argyrophilic cytoplasmic proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…reported that the rate of malignant transformation of GCT was extremely low (2%) 8 . In Japan, four patients with malignant GCT of the esophagus have been reported; 9–12 however, malignant transformation of colonic GCT has yet to be documented. Malignant transformation of GCT is often associated with an ulcer on the tumor surface and is histopathologically characterized by atypia of nuclei and severe infiltration of lymphocytes into the tumor stroma.…”
Section: Discussionmentioning
confidence: 99%
“…reported that the rate of malignant transformation of GCT was extremely low (2%) 8 . In Japan, four patients with malignant GCT of the esophagus have been reported; 9–12 however, malignant transformation of colonic GCT has yet to be documented. Malignant transformation of GCT is often associated with an ulcer on the tumor surface and is histopathologically characterized by atypia of nuclei and severe infiltration of lymphocytes into the tumor stroma.…”
Section: Discussionmentioning
confidence: 99%